2015
DOI: 10.1007/s10815-014-0426-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of late-start Corifollitropin-alfa administration for controlled ovarian hyperstimulation in IVF: a cohort, case–control study

Abstract: Objective To investigate efficacy and safety of a controlled ovarian stimulation (COS) protocol in which a single dose of Corifollitropin-alfa (CFα) was administered on day 4 of a GnRH-antagonist cycle. Design Cohort case-control study. Setting University Hospital. Patients One hundred twenty-two normally cycling women expected to be normal responders to COS. Interventions In 61 patients, CFα (100-150 μg) was injected subcutaneously on day 4 of a spontaneous menstrual cycle; a GnRH-antagonist was added from da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In comparative clinical trials, CF α was shown to be an effective alternative to daily injections of r-hFSH in COS [ 46 ]. Comparable results in terms of ongoing pregnancy rate, miscarriage rate, and live birth rate were reported with the use of CF α versus daily r-hFSH [ 47 ].…”
Section: Recombinant Human Fsh (R-hfsh)mentioning
confidence: 99%
“…In comparative clinical trials, CF α was shown to be an effective alternative to daily injections of r-hFSH in COS [ 46 ]. Comparable results in terms of ongoing pregnancy rate, miscarriage rate, and live birth rate were reported with the use of CF α versus daily r-hFSH [ 47 ].…”
Section: Recombinant Human Fsh (R-hfsh)mentioning
confidence: 99%